A perspective on how glyphosate and 2,4-D in wetlands may impact climate change - Cornish, Christine M.; Sweetman, Jon N. (Frontiers in Environmental Science, 2023)
An increase in herbicide use is occurring due to a growing population and herbicide-resistant crops in agriculture, which has resulted in more herbicide tolerant target species. Glyphosate and 2,4-Dichlorophenoxyacetic acid (2,4-D) are two of the most commonly used herbicides worldwide and are more recently being used in combination in pre-mixed commercial formulas. Subsequently, herbicide contamination of wetlands will increase exposure of microorganisms to multiple chemical stressors. Methane is a potent greenhouse gas naturally emitted from wetlands, but herbicides may disrupt biogeochemical processes leading to an unbalanced methane cycle. We review the impacts of these herbicides on aquatic microbial communities from glyphosate-derived nutrient enrichment and 2,4-D inhibition of methane oxidation, and examine how these altered metabolic processes may lead to increased methane production in wetlands. The response of wetland ecosystems to herbicide contamination will vary across regions, in part due to the complexity of microbial communities, however, this perspective gives a glimpse into the potential global implications of continuing herbicide use on wetlands and demonstrates the importance for research on ecosystem-level co-stressors.